Tipologi Fasad Bangunan Quonset Hut di Kota Balikpapan - Mallika Putri Santoso (Universitas Muhammadiyah Palembang, 2026)
Quonset Hut is a semi-permanent prefabricated building with a light steel structure and a curved corrugated roof, designed by the United States military during World War II as a barracks and storage warehouse. Although initially temporary, this building still survives in various countries, including Indonesia. In Balikpapan, Quonset Hut is known as